Summary of Twenty-First Century Great Conversations in Art, Neuroscience and Related Therapeutics - Juliet L. King (Frontiers in Psychology, 2018)
Transdisciplinary collaboration is the future of knowledge making in advanced post-industrial societies and there is a growing awareness that the most vexing problems we face cannot be solved by any single discipline. Best practices for complex and challenging physical and mental disorders require a multi-disciplinary approach, yet there is a void in bridging the gap between the most contemporary models. It is in this capacity that the Twenty-First Century Great Conversations in Art, Neuroscience, and Related Therapeutics serves as a missing link. It was with active minds and a collective spirit that artists, scientists, therapists, physicians, engineers, technology experts, healthcare practitioners, and researchers from across the globe transcended historical silos to explore the capacities for collaborative partnerships to influence the health of patients and the amelioration of disease. Hosted at Indiana University-Purdue University Indianapolis (IUPUI), presenters shared insights through didactic sessions and panel discussions aligned with three tracks led by prominent experts in their respective fields: (1) Neuroaesthetics, Anjan Chatterjee, MD; (2) Creativity and Consciousness, Arne Dietrich, PhD; and (3) Mobile Brain/Body Imaging (MoBI), Klaus Gramann, PhD. The goals for this symposium were developed from a vision which embraces cross-disciplinary intersectionality, a merging of viewpoints, and active dialogue surrounding the development of a common language with which to advance the Creative Arts Therapies and neurosciences. The goal was also to contribute to the development of a simplified roadmap to enhance and enrich the CATs with a greater understanding of neuroscience and the available technologies that can assist in research.